การนำเสนอรายวิชาการสื่อสารด้วยการพูดภาษาอังกฤษในงานโรงแรมสำหรับนักเรียนประกาศนียบัตรวิชาชีพ สาขาการจัดการโรงแรม วิทยาลัยเทคโนโลยีอาเซียน - ปริวรรตภาษา, วราวุธ; มีศรี, ราเชน (An Online Journal of Education, 2018)
This study was aimed 1) to assess the needs of hotel management students at ASEAN Technological College and 2) to propose a course syllabus of English Oral Communication in Hotel Jobs for the Lower Vocational Students in the Field of Hotel Management at this college. The participants of this study consisted of 5 stakeholders of hotels in Nong Khai and 36 lower vocational students in the field of hotel management at ASEAN Technological College. The data were collected by a semi-structured interview and a questionnaire. The findings revealed that 1) hotel management students need to learn and practice oral communication more in the situations of arranging the room reservation, giving information about the regulation for the hotel guests, giving the information about the hotel rooms and facilities, welcoming the hotel’s customer, and asking for the guest’s detail. They want to learn by inductive approach and practice English language use through the authentic activities. 2) The course syllabus of English Oral Communication in Hotel Jobs was proposed based on the students’ needs of language learning. Teaching and learning activities in the course need to be communicative and authentic activities The contents of the course covered these important situations of oral communication: arranging the room reservation; giving information about the regulation for the hotel guests; giving the information about the hotel rooms and facilities; welcoming the hotel’s customer; and asking for the guest’s detail.